Determinants of Stunting Among Children Aged 24–59 Months in Kuningan District, Indonesia - Nourma Nurjanah; Nova Oktavia; Teguh Tri Sutarno Putra (PT Bukuloka Literasi Bangsa, 2026)
ABSTRACT Stunting remains a persistent public health problem in Indonesia, including Kuningan District, where prevalence rates have shown fluctuating trends over recent years. In 2018, the prevalence of stunting was 8.2%, increasing slightly to 8.4% in 2019, declining to 5.4% during 2020–2021, and rising again to 6.6% in 2022. Stunting is a multifactorial condition influenced by inadequate parenting practices, limited access to health services, insufficient household food security, and poor water and sanitation conditions. This study aimed to analyze factors associated with stunting among children under five years of age in Kuningan District. This case–control study was conducted in Kuningan District, Indonesia. A total of 188 children aged 24–59 months were included, consisting of 94 stunted children (cases) and 94 non-stunted children (controls), selected using purposive sampling. Data were collected using structured questionnaires and analyzed using the Chi-square test to identify associations between independent variables and stunting incidence. The main findings indicated significant associations between maternal education level (p = 0.001), milk consumption patterns (p = 0.029), and parenting practices (p = 0.027) with stunting among children under five. In contrast, no significant associations were found between family income (p = 0.166) and the age of complementary feeding initiation (p = 0.228) with stunting. By identifying key maternal and behavioral factors associated with stunting, this study contributes to a better understanding of childhood stunting determinants at the district level. The findings highlight the importance of improving maternal education and child feeding practices as strategic interventions to reduce stunting prevalence. Future research should explore broader contextual and longitudinal factors to strengthen stunting prevention efforts in public health practice. KEYWORDS: Stunting; maternal education; family income; milk consumption; complementary feeding; parenting practices